If $A, B, C$ are angles of $\Delta ABC$ and $\sin (A-\pi /4) \sin (B-\pi/4) \sin (C-\pi/4)=\frac{1}{2\sqrt 2}$, then prove that $\sum \tan A \tan B=\sum \tan A$

Solving the given equation, we get$$(\sin A-\cos A)(\sin B -\cos B)(\sin C -\cos C)=1$$ $$(\tan A-1)(\tan B-1)(\tan C-1)=\sec A \sec B \sec C$$ $$\sum \tan A -\sum \tan A \tan B +\sum \tan A-1=\sec A \sec B \sec C$$

How should I proceed?



Both \begin{align} \sin (A-\pi /4) \sin (B-\pi/4) \sin (C-\pi/4)=\frac{1}{2\sqrt 2} \tag{1}\label{1} \end{align}

and \begin{align} \tan A\tan B+\tan B\tan C+\tan C\tan A &= \tan A+\tan B+\tan C , \tag{2}\label{2} \end{align}

expressed in terms of semiperimeter $\rho$, inradius $r$ and circumradius $R$ of the triangle, are equivalent to

\begin{align} \rho^2&=r^2+4\,r\,R+2\,\rho\,r \tag{3}\label{3} , \end{align}

which implies

\begin{align} \rho&=r+\sqrt{2\,r^2+4\,r\,R} \tag{4}\label{4} . \end{align}

But \eqref{4} is true only for the degenerate triangle when one angle is $180^\circ$ and the other two are zero.

For the conversion, use known identities for the angles of triangle

\begin{align} \cos A\cos B\cos C&=\frac{r}{R}+1 \tag{5}\label{5} ,\\ \sin A\sin B\sin C &= \frac{\rho\,r}{2R^2} \tag{6}\label{6} , \end{align}

\begin{align} \tan A\tan B\tan C = \tan A+\tan B+\tan C &=\frac{2\rho\,r}{\rho^2-(r+2\,R)^2} \tag{7}\label{7} ,\\ \tan A\tan B+\tan B\tan C+\tan C\tan A &=1+\frac{4\,R^2}{\rho^2-(r+2\,R)^2} \tag{8}\label{8} ,\\ \cot A+\cot B+\cot C&= \frac12\,\left(\frac{\rho}r -\frac r\rho \right) -2\,\frac R\rho \tag{9}\label{9} . \end{align}

| cite | improve this answer | |
  • $\begingroup$ Isn’t $\sum \tan A = \tan A \tan B \tan C$? You have written $\tan A \tan B \tan C =\sum \tan A \tan B$ $\endgroup$ – Aditya Mar 17 at 18:35
  • $\begingroup$ @Aditya: Yes, of course, in \eqref{2} $\sum\tan A\tan B=\sum\tan A=\prod\tan A=\frac{2\rho\,r}{\rho^2-(r+2\,R)^2}$. $\endgroup$ – g.kov Mar 17 at 18:47

From the given,

$$0=\frac{1}{2\sqrt 2}- \sin (A-\pi /4) \sin (B-\pi/4) \sin (C-\pi/4)$$

$$=\frac{1}{2\sqrt 2}-\frac12\left[ \cos(A-B)-\cos(A+B-\frac\pi2)\right] \sin (C-\pi/4)$$ $$\frac{1}{2\sqrt 2}[ 1- (\cos(A-B)-\sin C) (\sin C - \cos C)]$$

Note that $\cos(A-B)\le 1$, and $$0 \ge \frac{1}{2\sqrt 2}[1-( 1 -\sin C ) (\sin C - \cos C)]$$ $$ = \frac{1}{2\sqrt 2}[(1+\cos C) - \sin C (1+\cos C - \sin C) ]$$ $$ = \frac{1}{2\sqrt 2}[2\cos^2 \frac C2- \sin C (2\cos^2 \frac C2 - 2\sin \frac C2\cos\frac C2)] $$ $$ = \frac{1}{\sqrt 2}\cos^2 \frac C2\left[1- 2\sin\frac C2(\cos \frac C2 - \sin \frac C2)\right] $$ $$ = \frac{1}{\sqrt 2}\cos^2 \frac C2(2- \sin C - \cos C ) $$

So, $$0 \ge \cos^2 \frac C2(2- \sin C - \cos C ) \implies \cos\frac C2=0$$

which leads to $C = \pi$ and $A=B = 0$. Thus,

$$ \tan A\tan B+\tan B\tan C+\tan C\tan A = \tan A+\tan B+\tan C =0 $$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.